2022
DOI: 10.1155/2022/6547461
|View full text |Cite
|
Sign up to set email alerts
|

Development of Starch-Based Bioplastic from Jackfruit Seed

Abstract: In this article, jackfruit seed starch plasticized with common plasticizers was developed and characterized. At the first step, the research papers that dealt with the fabrication and characterization of starch-based bioplastics were synthesized and analyzed. Next, jackfruit seeds were selected as a source for starch because of their large availability, low price or even free, and high starch capacity. Afterward, a starch-based bioplastic fabrication procedure was proposed. From preliminary tests, plasticizers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Generally, mechanical properties can be improved by fiber surface treatments, addition of plasticizers and cross-linking agents [ 170 , 171 , 172 , 173 ]. Most researchers focus on mechanical properties as part of their investigation.…”
Section: Properties Of Biocomposites Based Cornmentioning
confidence: 99%
“…Generally, mechanical properties can be improved by fiber surface treatments, addition of plasticizers and cross-linking agents [ 170 , 171 , 172 , 173 ]. Most researchers focus on mechanical properties as part of their investigation.…”
Section: Properties Of Biocomposites Based Cornmentioning
confidence: 99%
“…Comparing this result with other starch-based biocomposites such as Jackfruit seed starch [ 60 ] and potato starch [ 61 ] reveals that plasticizing starch with a load of (15–35%) shows good tensile strength while maintaining acceptable flexibility. However, the effect of ultrasound treatment on the mechanical properties needs more investigation, especially for the aspect of the molecular structure.…”
Section: Resultsmentioning
confidence: 83%
“…In another study, Lubis et al ( 45 ) investigated bioplastics made of jackfruit seed starch plasticized with glycerol. Jackfruit seed starch plasticized with common plasticizers was also characterized by other researchers ( 46 ). Early tests showed that water, glycerol, sodium bicarbonate, and citric acid were among the plasticizers that worked well enough.…”
Section: Applications Of Jackfruit's Bioproductsmentioning
confidence: 77%
“…After making four different types of bioplastics with different combinations of these plasticizers, the properties of these synthesized bioplastics were analyzed. Bioplastics made through biological processes using renewable biomass showed great promise as a material of the future due to their sustainability and high potential ( 46 ).…”
Section: Applications Of Jackfruit's Bioproductsmentioning
confidence: 99%